2012
DOI: 10.5858/arpa.2011-0447-oa
|View full text |Cite
|
Sign up to set email alerts
|

Mucinous Carcinomas of the Gallbladder: Clinicopathologic Analysis of 15 Cases Identified in 606 Carcinomas

Abstract: Mucinous carcinomas constitute 2.5% of GB carcinomas. They present with an acute cholecystitis-type picture. Most MCs are a mixed-mucinous, not pure colloid, type. They are typically large and advanced tumors at the time of diagnosis and thus exhibit more-aggressive behavior than do ordinary GB carcinomas. Immunophenotypically, they differ from conventional GB adenocarcinomas by MUC2 positivity, from intestinal carcinomas by an often inverse CK7/20 profile, from pancreatic mucinous carcinomas by CDX2 negativit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(74 citation statements)
references
References 57 publications
4
61
2
Order By: Relevance
“…They are typically large and advanced tumours at the time of diagnosis, with 87% of the cases showing T3 tumours, as opposed to 48% in conventional GB adenocarcinomas, and thus exhibit more-aggressive behavior than conventional GB carcinomas. 4 They may lead to pseudomyxoma peritonei. Giang et al, in a review of 23 GB carcinomas, discussed the potential pitfall of confusing primary mucinous adenocarcinoma of GB with pseudomyxoma peritonei from a low-grade appendiceal neoplasm disseminated to GB, especially when only the GB is removed.…”
Section: 3mentioning
confidence: 99%
See 3 more Smart Citations
“…They are typically large and advanced tumours at the time of diagnosis, with 87% of the cases showing T3 tumours, as opposed to 48% in conventional GB adenocarcinomas, and thus exhibit more-aggressive behavior than conventional GB carcinomas. 4 They may lead to pseudomyxoma peritonei. Giang et al, in a review of 23 GB carcinomas, discussed the potential pitfall of confusing primary mucinous adenocarcinoma of GB with pseudomyxoma peritonei from a low-grade appendiceal neoplasm disseminated to GB, especially when only the GB is removed.…”
Section: 3mentioning
confidence: 99%
“…Immunophenotypically, mucinous carcinomas of gall bladder differ from intestinal carcinomas by an inverse CK7/20 profile, and from pancreatic mucinous carcinomas by CDX2 negativity (Figure 4). 4 The risk factors, associated features, natural history and prognosis of mucinous carcinoma of GB are not very well known, owing to their extreme rarity. They are typically large and advanced tumours at the time of diagnosis, with 87% of the cases showing T3 tumours, as opposed to 48% in conventional GB adenocarcinomas, and thus exhibit more-aggressive behavior than conventional GB carcinomas.…”
Section: 3mentioning
confidence: 99%
See 2 more Smart Citations
“…[4][5][6] The risk factors for all gall bladder carcinoma are gall stones, calcified porcelain gall bladder, choledochal cyst, polypoid lesion of the gall bladder, sclerosing cholangitis, anomalous pancreaticobiliary junction and exposure to carcinogens. [4][5][6] In recent analysis of 15 cases gall bladder carcinoma, 67% patients presented with clinical picture of acute cholecystitis such pain in right hypochondriac region and vomiting. 4 They observed that these tumours are generally large and advanced at the time of diagnosis, so they have more aggressive behavior than conventional adenocarcinoma of gall bladder.…”
Section: Case Reportmentioning
confidence: 99%